Behavioural adaptation to in-vehicle navigation systems - Forbes, Nicholas Lloyd (2009)
This PhD investigates driver behavioural adaptation to in-vehicle navigation systems (IVNS). Behavioural adaptation is receiving an increasing amount of research attention in traffic psychology, but few studies have directly considered the concept in relation to IVNS. The thesis aims were addressed using a range of quantitative and qualitative methodologies.